Custom-made polyurethane-based synthetic bones mimic screw cut-through of intramedullary nails in human long bones. (May 2021) - Hollensteiner, Marianne; Sandriesser, Sabrina; Hackl, Simon; Augat, Peter
Abstract: Intramedullary nails are considered the gold standard for the treatment of tibial shaft fractures. Thereby, the screw-bone interface is considered the weakest link. For biomechanical evaluation of osteosyntheses synthetic bones are often used to overcome the disadvantages of human specimens. However, commercially available synthetic bones cannot adequately mimic the local mechanical properties of human bone. Thus, the aim of this study was to develop and evaluate novel cortical bone surrogate materials that mimic human tibial shafts in the screw-loosening mechanisms of intramedullary nails. Bone surrogates, based on two different polyurethanes, were developed and shaped as simple tubes with varying cortical thicknesses to simulate the diaphyseal cortex of human tibiae. Fresh frozen human tibiae and commercially available synthetic bones with similar cortical thickness were used as references. All specimens were treated with a nail dummy and bicortical locking screws to simulate treatment of a distal tibia shaft fracture. The nail-bone construct was loaded in a combined axial-torsional-sinusoidal loading protocol to simulate the physiological load during human gait. The loads to failure as well as the number of load cycles were evaluated. Furthermore, the cut-through length of the screws was analysed by additional micro computed -tomography images of the tested specimens. The failure load of custom made synthetic bone tubes with 6 mm cortical thickness (3242 ± 136 N) was in accordance with the failure load of human samples (3300 ± 307 N, p = 0.418) with a similar cortical thickness of 4.9 ± 1.4 mm. Commercially available synthetic bones with similar cortical thickness of 4.5 ± 0.7 mm were significantly stronger (4575 ± 795 N, p = 0.008). Oval-shaped migration patterns were "cut" into the cortices by the screws due to the cyclical loading. The cut-through length of the self-developed synthetic bones with 6 mm cortices (0.8 ± 0.6 mm, p = 0.516) matched the cut-through of the human tibiae (0.7 ± 0.6 mm). The cut-through of commercially available epoxy-based synthetic bones deviated from the human reference (0.2 ± 0.1 mm, p < 0.001). The results of this study indicate that the novel bone surrogates realistically mimic the failure and screw migration behaviour in human tibiae. Thus, they offer a new possibility to serve as substrate for biomechanical testing. The use of commercially available surrogates is discouraged for biomechanical testing as there is a risk of drawing incorrect conclusions.